Penerapan Metode Tutor Sebaya Untuk Meningkatkan Hasil Belajar Siswa Kelas VII Dalam Pembelajaran Seni Tari Di SMP Negeri 3 Kota Solok - Wike Wulan Dari; Yuliasma Yuliasma; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2019)
This article aims to find out the application of the method of Peer Tutors in Class VII in learning the art of dance in SMP Negeri 3 Kota Solok. This type of research this is a class action Research (PTK). The object of research is the grade VII in the SMP Negeri 3 Solok which consists of 30 students. Research instrument is the Researcher as a teacher practitioners, teachers of art and culture as an Observer and the observation sheet tools, documentation, and test the ability of the students. Further data was collected with the data analysis techniques to selected and analyzed his righteousness. The results of this research show that the application of the method of Peer Tutors in SMP Negeri 3 Solok in 2 cycle with 5 times the meeting went well and smoothly. Improved student learning outcomes can be seen from the goal of learning the art of dance with smooth motion and assessment aspects. The average student learning outcomes i.e. 74 category I cycle quite well with the average percentage of 48.3% ketuntasan I cycle and which are not comprehensively 51.65%. Then average the results of student learning cycle II 86 categories very well with the average percentage of 98.3% in cycle II ketuntasan and its not finished 16.6%. Thus the results of this study indicate that the peer tutor methods can improve the results of learning the art of dance class VII in SMP Negeri 3 Solok.